Consistent effects of eastern subterranean termites (Reticulitermes flavipes) on properties of a temperate forest soil. (December 2015) - Neupane, Avishesh; Maynard, Daniel S.; Bradford, Mark A.
Abstract: Termites inhabit a large portion of land covered by temperate forests. Climate warming and urbanization will likely extend their range and increase their densities in these ecosystems but, compared to their tropical counterparts, little is known about their effects on soil properties and processes. If temperate termites have the strong ecosystem engineering effects of tropical termites, then knowledge of their ecology and impacts will be vital for predicting how temperate systems respond to environmental change. We investigated how feeding and tunneling by the eastern subterranean termite, Reticulitermes flavipes, affected wood decomposition and soil properties under decaying wood. Twelve laboratory microcosms filled with mineral soil and with wood blocks of four common temperate tree species, received R. flavipes soldiers and workers at field densities, with an additional five termite-free microcosms serving as controls. After 25 weeks, the effects of termites on wood mass loss, and on carbon and nitrogen dynamics, differed across tree species, yet their effects on soil properties were consistent regardless of wood type. Microbially-available carbon in soil was 20% higher with termites and soil moisture content 20% lower. Soil pH was more acid with termites and their effects on soil microbial biomass were positive but non-significant. These soil responses were consistent regardless of the wood species, suggesting that termite effects on soil are dictated largely by their activity within the soil matrix and not by their feeding rate on specific wood substrates. These results are among the first to quantify the effects of temperate forest termite activity on soil properties, demonstrating the potential for these termites to shape biogeochemical cycling and plant communities through their alteration of the soil environment. Highlights: Effect of eastern subterranean termites' wood-feeding activity on soil was studied. Termites increased wood mass loss and microbially-available carbon in soil. Termites decreased soil moisture and pH. Termites' effect on soil properties were consistent across the four wood species. The effects on wood mass loss, carbon and nitrogen dynamics were species dependent.